Seasonal variation in water quality and fish diversity of Rampur Ghol, a wetland in Chitwan, Central Nepal - Oli, Bam Bahadur; Jha, Dilip Kumar; Aryal, Prakash Chandra; Shrestha, Madhav Kumar; Dangol, Dharma Raj; Gautam, Birendra (Nepalese Journal of Biosciences, 2013)
The present study was carried out on Rampur Ghol in three seasons viz., monsoon, post-monsoon and pre-monsoon from September, 2012 to April, 2013 to assess the seasonal variation in physico-chemical parameters of water and fish diversity. The analysis of various physico-chemical parameters showed significant seasonal fluctuation in the water quality. However, the Ghol water was found to be suitable for fish fauna. Similarly, fish diversity analysis showed that Rampur Ghol is rich in fish fauna with 22 species belonging to 13 families and five orders. The study showed significant decline of fish species as well as their abundance from past studies.